Waking the Dead : The Glory of a Heart fully Alive] - Eldredge, John, 1960-; Dolan, Kelly Ryan (Carol Stream, IL : Oasis Audio, 2003)
Waking the dead will help you find out how to become all God meant you to be : make you whole, set you free, bring you fully alive
Subtitle from container
Compact discs
"Tracks every 3 minutes for easy bookmarking"--Box
Read by Kelly Dolan ; special introduction by John Eldredge
Keywords: Christian life; Spiritual life -- Christianity; Audiobooks